PELAKSANAAN BAGI HASIL TERNAK SAPI PERAH DI DESA KEPUHARJO KECAMATAN CANGKRINGAN KABUPATEN SLEMAN DIKAITKAN DENGAN UU NOMOR 6 TAHUN 1967 - , Alfilia Putri Vidityasari, S.H; , Sri Natin, S.H., S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was intended to study yield sharing system of dairy cattle and to identify resolution of dispute between dairy cattle owner and keeper in Kepuharjo village of Cangkringan district, Sleman. It was juridical empirical research which is based on field study to obtain primary data. Primary data were obtained by interviewing informant. Literary study to obtain secondary data. The data were formulated systematically and analyzed qualitatively. Primary data were obtained in field by interview with 16 respondents and 4 informants using interview guide. The result indicated that yield sharing system of dairy cattle used maro bathi ( the yield is divided by two ). The yield sharing includes calf and milk product. Calf sharing was done by maro bathi, when both parties did not want to sell the calf, the sharing was done by rotation system, in which the first calf is owned by keeper, and the next is for its owner. The system prevails also for milk product after milk is sold to cooperation. Result of milk sale is divided into two parts for keeper and owner. The research also indicated that dispute between cow keeper and owner is resolved by familial way and involve third party. Keywords: maro bathi, dispute resolution and adat law